Human activity recognition based on smartphone sensors - Rajendran, Abinaya (2019)
Human Activity Recognition otherwise called as HAR is a challenging research field that promotes quality of life by means of ambient intelligence and assisted living. The fundamental step for the development of intelligent system is to understand and start learning the human activities in the real time environment. Numerous ways for recognizing the human activities are being proposed by the researchers over the last decade. Some of these methods are discussed in this dissertation work and an attempt has been made to utilize them to recognize the human activities.